2011
DOI: 10.1097/prs.0b013e31821740ff
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the Internal Mammary Artery

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…1 As SNB has become commonly used, the TDA/V are not favored because of the invasive and time-consuming process. [7][8][9] In contrast, the IMA/V have gained popularity following reports on the use of the ribsparing technique, 16,20 end-to-side anastomosis, 18,21 anastomosis to internal mammary vessel perforator, [22][23][24] and flow-through anastomosis 25 to address problems. However, axillary vessels such as the TDA/V are important because reconstruction can be performed with only a lateral incision without creating a conspicuous anterior scar.…”
Section: Discussionmentioning
confidence: 99%
“…1 As SNB has become commonly used, the TDA/V are not favored because of the invasive and time-consuming process. [7][8][9] In contrast, the IMA/V have gained popularity following reports on the use of the ribsparing technique, 16,20 end-to-side anastomosis, 18,21 anastomosis to internal mammary vessel perforator, [22][23][24] and flow-through anastomosis 25 to address problems. However, axillary vessels such as the TDA/V are important because reconstruction can be performed with only a lateral incision without creating a conspicuous anterior scar.…”
Section: Discussionmentioning
confidence: 99%
“…However, cadaveric studies may be unreliable due to the lack of pulsation and the presence of vascular contraction. Clinical studies have reported average external diameter of arterial perforators being 1.32–1.52 mm and venous perforator diameter being 1.4–2.2 mm (Apostolides et al, 2011; Arnez et al, 1995; Baek et al, 2013; Dupin et al, 1996; Fansa et al, 2013; Follmar et al, 2011; Guzzetti & Thione, 2001; Haywood et al, 2003; Kanoi et al, 2017; Ninković et al, 1995; Park et al, 2003; Rosson et al, 2005; Saint‐Cyr et al, 2007; Saour et al, 2017; Schmidt et al, 2010; Vesely et al, 2007). The largest arterial and venous perforator diameter reported were 2.5 and 2.2 mm, respectively (Baek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Predictably, the failure rates documented in these studies are far higher than in breast reconstruction using ETS arterial anastomoses. 54,55 The variability of results between these large studies using the one anastomosis technique demonstrates many factors at play in free flap success rates. More broadly, Cho et al’s 53 findings are supported by clinical evidence showing equivalent long-term patency rates for ETE and ETS anastomoses in free tissue transfer to various anatomic sites.…”
Section: Discussionmentioning
confidence: 99%